The plantar calcaneal spur: a review of anatomy, histology, etiology and key associations. Issue 6 (29th March 2017) - Kirkpatrick, Joshua; Yassaie, Omid; Mirjalili, Seyed Ali
Abstract: The plantar calcaneal spur (PCS) is a bony outgrowth from the calcaneal tuberosity and has been studied using various methods including cadavers, radiography, histology and surgery. However, there are currently a number of discrepancies in the literature regarding the anatomical relations, histological descriptions and clinical associations of PCS. Historically, authors have described the intrinsic muscles of the foot and/or the plantar fascia as attaching to the PCS. In this article we review the relationship between the PCS and surrounding soft tissues as well as examining the histology of the PCS. We identify a number of key associations with PCS, including age, weight, gender, arthritides, plantar fasciitis and foot position; these factors may function as risk factors in PCS formation. The etiology of these spurs is a contentious issue and it has been explained through a number of theories including the degenerative, inflammatory, traction, repetitive trauma, bone‐formers and vertical compression theories. We review these and finish by looking clinically at the evidence that PCS causes heel pain.